FAKTOR YANG MEMENGARUHI KEMITRAAN KONTRAKTOR DAN PERANCANG DALAM PROYEK DESIGN AND BUILD - Sutowo, Achmad; Irawan, Agustinus Purna; Murtiana Sari, Endah; Fuk Jin, Oei (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2026)
The government is currently encouraging readiness in government projects using the Design & Build project delivery system, as regulated in the Construction Services Law No. 7 of 2017. Design and Build (DB) from various previous literature has been proven to provide advantages compared to Design Bid Build (DBB) including speed of implementation, project risks, design changes and the absence of change orders during project implementation. This study aims to examine what factors influence the partnership of contractors and designers in design and build projects to produce good project performance including cost, quality, time, K3 and environment. The research method used in this study is a quantitative method with 50 respondents and processed through SPSS to explore respondents' perceptions, about factors that are considered to influence the partnership of contractors and designers in Design and Build (DB) projects. The respondents came from contractors and consultants who have worked on government projects with design & build project delivery. The results of this study indicate six key factors influencing contractor–designer partnerships in Design and Build projects, including relationship factors, process factors, and environmental factors, with partnership maturity acting as a moderating variable. These factors contribute to improved project performance in terms of cost, quality, time, safety, and environmental aspects. The findings provide practical insights for contractors and designers in strengthening collaboration and readiness for implementing Design and Build project delivery systems.